1999
DOI: 10.1103/physrevb.59.9642
|View full text |Cite
|
Sign up to set email alerts
|

Doping dependence of the pseudogap inLa2xSrxCuO

Abstract: We report the results of Raman scattering experiments on single crystals of La 2Ϫx Sr x CuO 4 that span the range from underdoped (xϭ0.10) to overdoped (xϭ0.22). The spectra are consistent with the existence of a strong anisotropic quasiparticle interaction that results in a normal state depletion of spectral weight from regions of the Fermi surface located near the zone axes. The strength of the interaction decreases rapidly with increasing hole concentration and the spectral evidence for the pseudogap vanish… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
65
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 65 publications
17
65
0
Order By: Relevance
“…Being a two-particle probe, ERS is able to access the charge dynamics in both the normal and the superconducting states. 8,9,10,11 Moreover, through the use of particular sets of incident and scattered polarizations, it is able to probe different regions of the Fermi surface, i.e. the nodal (along the (0,0)-(π, π) direction) and antinodal (along the (0,0)-(π, 0) direction) quasiparticles.…”
mentioning
confidence: 99%
“…Being a two-particle probe, ERS is able to access the charge dynamics in both the normal and the superconducting states. 8,9,10,11 Moreover, through the use of particular sets of incident and scattered polarizations, it is able to probe different regions of the Fermi surface, i.e. the nodal (along the (0,0)-(π, π) direction) and antinodal (along the (0,0)-(π, 0) direction) quasiparticles.…”
mentioning
confidence: 99%
“…In the B 1g channel the intensity of the pair-breaking peak decreases continuously when approaching the underdoped range of the phase diagram which goes along with a strong suppression of the overall Raman intensity. This effect may be caused by a change of the Fermi surface (FS) topology and is also seen in YBa 2 Cu 3 O 6+x [1] and La 2−x Sr x CuO 4 [2]. The low frequency behavior of the SC spectra is shown in Fig.…”
mentioning
confidence: 95%
“…Both appear at nearly the same energy, exhibit similar doping dependence and possibly have the same physical origin. [4,5,9,10] It is interesting also to note that in the materials where the MIR peak appears at a relatively small energy, comparable with the typical damping energy Σ ≡ /τ [7,8], there is an essential difference between the predictions of the usual one-band optical models and measurements. It is explicitly shown that the development of the measured MIR structure with temperature can be fitted well with the orbital Kondo model of Emery and Kivelson [19] (representing the regime where ω ir peak ≈ Σ) rather than with the mentioned one-band models (underdamped regime: ω ir peak is proportional to characteristic correlation energy scales, such as the Hubbard interaction U [11,12] or the AF exchange energy J [13]).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is also accompanied by several anomalies regarding the relative spectral weights of three Raman polarizations. [3,9,10] Actually, the recent interest in the Drude part of the optical conductivity and Raman scattering spectra of the underdoped compounds is stimulated by the clear evidence for important role of the normal-state coherence effects. The optical conductivity and B 2g Raman spectra scan the electronic states in the nodal region of the Fermi surface (so-called "cold spots" on the Fermi surface: k x = k y ), while the A 1g and B 1g Raman scattering processes probe the electronic states in the vicinity of the van Hove points ("hot spots").…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation